Strategi Peningkatan Daya Saing Usaha Kecil dan Menengah (UKM) Berbasis Kaizen - Andi Suranta Meliala; Nazaruddin Matondang; Rahmi M Sari (Jurnal Optimasi Sistem Industri, 2014)
The economy was one factor the progress of a country. Each country competing to increase the productivity of the economy. Indonesia's economy ranks 17 world. Economic growth in Indonesia is very significant that was not separated from the role of small and medium enterprises (SMEs) that support the growth of exports and imports, one that can be seeded SMEs are SMEs manufacture of shoes. The role of SMEs that are so large and significant must always be maintained and developed to be able to compete in an era of global competition such as the implementation of the Asean Economic Community (AEC) in January 2015. Problems that interfere with the development and productivity of SMEs shoes, particularly around Medan city will be divided into 4 categories, namely: (1) human, (2) process, (3) facilities, and (4) Business competition. Based on this research, it is known that the most important issues that affect the development of SMEs in Medan shoe is its human resources. Solving these problems will be done with the Kaizen strategy (5S) which will be combined with the concept of training within industry (TWI) and the concept of P-Course. These improvements will result in strategies to increase the overall productivity of SMEs working with the primary focus is working and will evaluate the system works. This strategy is expected to fix the weaknesses of existing SMEs shoes, in order to face the global competition that will come.